Control of Panicum zizanoides H.B.K. and Paspalum conjugatum Beg. under several strategies of management in banana (Musa AAA) plantation. - Acosta-Arce, Luis; Agüero-Alvarado, Renán (Agronomía Mesoamericana, 2006)
The objective of this study was to determine the effect of several management strategies on the populations of these species. A ten-year-old banana plantation was chosen for evaluation with the following treatments: T1 = untreated control; T2= physical control, T3= successive sprays with glyphosate, T4= successive sprays with paraquat, T5= successive sprays with gluphosinate and T6= mixed control based on weed sampling. Populations of P. zizanoides in rows were reduced 89, 93, 79 and 68% for T3,T4, T5, T6 respectively compared with T1. In the area next to the banana plant, populations of P. conjugatum were reduced by 78, 91, 95, 99 and 75% for T2, T3, T4, T5 and T6 respectively (Duncan; p< 0.05). The results indicate that treatments with herbicides and mixed control reduce the populations of these species, while populations of the untreated and physical control plots remained constant in time.